Techpreneur: the padlet edition - Mohamed, Suhana; Zainuddin, Atiqah Najwa; Mohd Yusoff, Razieman; Mohd Ridzwan, Elyn (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
TechPreneur: The Padlet Edition is an interactive learning tool that helps students excel in their entrepreneurship classes. It is an engaging and fun way for students to learn about entrepreneurship and technology. This edition is basically to help students manage their 1-semester class to keep on track with what they need to understand, learn, and experience. This padlet will also help the students to understand and learn how to score the subject. It also teaches students how to think critically and solve problems and generates an early interest in business. What has been used by the lecturers will also help the student as an educational tool. It also would be a great way to teach entrepreneurship and technology simultaneously as ideas to make it more fun and interactive. The padlet is used as an additional tool to help students to understand, be user-friendly, and have fun utilizing tools. It also promotes active learning and critical thinking, allowing for a deeper understanding of the subject. The tool is designed to help the students connect with the economics better, sparking more interest in the subject and building important skills for those who want to be entrepreneurs in the future